Anatomical subgroup analysis of the MERIDIAN cohort: posterior fossa abnormalities. (8th November 2017) - Griffiths, P. D.; Brackley, K.; Bradburn, M.; Connolly, D. J. A.; Gawne‐Cain, M. L.; Kilby, M. D.; Mandefield, L.; Mooney, C.; Robson, S. C.; Vollmer, B.; Mason, G.
ABSTRACT: Objective: To assess the diagnostic and clinical contribution of fetal magnetic resonance imaging (MRI) in fetuses of the MERIDIAN cohort diagnosed with abnormalities of the posterior fossa as the only intracranial abnormality recognized on antenatal ultrasound. Methods: This was a subgroup analysis of the MERIDIAN study of fetuses with abnormalities of the posterior fossa (with or without ventriculomegaly) diagnosed on antenatal ultrasound in women who had MRI within 2 weeks of ultrasound and for whom outcome reference data were available. The diagnostic accuracy of ultrasound and MRI is reported, as well as indicators of diagnostic confidence and effects on prognosis and clinical management. Appropriate diagnostic confidence was assessed by the score‐based weighted average method, which combines diagnostic accuracy with diagnostic confidence data. Results: Abnormalities confined to the posterior fossa according to ultrasound were found in 81 fetuses (67 with parenchymal and 14 with cerebrospinal fluid‐containing lesions). The overall diagnostic accuracy for detecting an isolated posterior fossa abnormality was 65.4% for ultrasound and 87.7% for MRI (difference, 22.3% (95% CI, 14.0–30.5%); P  < 0.0001). There was an improvement in 'appropriate' diagnostic confidence, as assessed by the score‐based weighted average method ( P  < 0.0001), and a three‐fold reduction in 'high confidence but incorrect diagnosis' was achieved using MRI. Prognostic information given to the women changed after MRI in 44% of cases, and the overall effect of MRI on clinical management was considered to be 'significant', 'major' or 'decisive' in 35% of cases. Conclusions: Our data suggest that any woman whose fetus has a posterior fossa abnormality as the only intracranial finding on ultrasound should have MRI for further evaluation. This is on the basis of improved diagnostic accuracy and confidence, which impacts substantially on the prognostic information given to women as well as their clinical management. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.